2002
DOI: 10.1038/sj.bdj.4801473a
|View full text |Cite
|
Sign up to set email alerts
|

Crowns and other extra-coronal restorations: Try-in and cementation of crowns

Abstract: Having successfully negotiated the planning, preparation, impression and prescription of your crown, the cementation stage represents the culmination of all your efforts. This stage is not difficult, but a successful outcome needs as much care as the preceding stages. Once a restoration is cemented there is no scope for modification or repeat. You have to get it right first time. Decemented crowns often have thick layers of residual cement suggesting problems with either initial seating or cement handling. Whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…After training, younger and older operators achieved similar accuracy to the control group with only T3. A previous study on computer learning research found that age did not affect the performance of experienced operators, 38 and the findings from this study may suggest that the tested training program was sufficient for T3, but not for TD. This finding may also be interpreted as younger operators' tendency to learn faster, particularly with TD, which may be less user-friendly and operator-dependent.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…After training, younger and older operators achieved similar accuracy to the control group with only T3. A previous study on computer learning research found that age did not affect the performance of experienced operators, 38 and the findings from this study may suggest that the tested training program was sufficient for T3, but not for TD. This finding may also be interpreted as younger operators' tendency to learn faster, particularly with TD, which may be less user-friendly and operator-dependent.…”
Section: Discussionsupporting
confidence: 47%
“…Conventional impressions were made by one operator in each center, who was trained in the study protocol for impression making and gypsum pouring. Impressions were made from both jaws of each volunteer, with the 1-step double mix technique 38 by using stock impression trays (Disposable impression trays; 3 M, Saint Paul, MN, USA) and polyvinyl siloxane impression material (3 M Express 2 Penta Putty and Light Body Standard; 3 M, Saint Paul, MN, USA). Each impression was poured into type IV gypsum (Fujirock EP; GC Corp, Tokyo, Japan) that was prepared with 20 mL of liquid per 100 g of hard gypsum stone.…”
Section: Methodsmentioning
confidence: 99%
“…Vita zirconia veneering glass ceramics were also chosen due to their worldwide clinical use and their CTE, which is compatible with the CTE of Ceramill ZI copings as mentioned earlier. The specimens were cemented over the CoCr dies using conventional glass ionomer cement due to its acceptable film thickness, ease of manipulation, and low cost …”
Section: Discussionmentioning
confidence: 99%
“…Durable bonding between dentin and luting material is one of the most important factors in avoiding detachment of restorations, as well as the prevention of microleakage, secondary dental caries and tooth fracture 15,22,23 . Various cements, such as zinc phosphate, zinc polycarboxylate, conventional glass‐ionomer cements and resin‐based cements, have been used as luting materials 24–26 …”
Section: Introductionmentioning
confidence: 99%